2022
DOI: 10.1093/hr/uhab042
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics data integration provides insights into the post-harvest biology of a long shelf-life tomato landrace

Abstract: In this study we investigated the transcriptome and epigenome dynamics of the tomato fruit during post-harvest in a landrace belonging to a group of tomatoes (Solanum lycopersicum L.) collectively known as “Piennolo del Vesuvio”, all characterized by a long shelf-life. Expression of protein-coding genes and microRNAs as well as DNA methylation patterns and histone modifications were analysed in distinct post-harvest phases. Multi-omics data integration contributed to the elucidation of the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…NASA scientists have also explored microgreens in space due to dynamic properties like the availability of oxygen generation, nitrogen, essential nutrients, and photoactive compounds to enhance the morale of astronauts during stretched stays away from Earth ( Kyriacou et al, 2017 ). Several breeding approaches and multiOmics have been explored to augment the shelf life, developmental rate and nutrient content of vegetables and fruits ( Kalia and Singh, 2018 ; Mathiazhagan et al, 2021 ; Reda et al, 2021 ; Valdes et al, 2021 ; AieseCigliano et al, 2022 ; Chakravorty et al, 2022 ; Dutta et al, 2022 ; Kumari et al, 2022 ; Parmar et al, 2022 ; Sahoo et al, 2022 ; Sharma et al, 2022 ). However, it has been observed in tomatoes that the dominance component was higher than the additive component for shelf life ( Pavan and Gangaprasad, 2022 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…NASA scientists have also explored microgreens in space due to dynamic properties like the availability of oxygen generation, nitrogen, essential nutrients, and photoactive compounds to enhance the morale of astronauts during stretched stays away from Earth ( Kyriacou et al, 2017 ). Several breeding approaches and multiOmics have been explored to augment the shelf life, developmental rate and nutrient content of vegetables and fruits ( Kalia and Singh, 2018 ; Mathiazhagan et al, 2021 ; Reda et al, 2021 ; Valdes et al, 2021 ; AieseCigliano et al, 2022 ; Chakravorty et al, 2022 ; Dutta et al, 2022 ; Kumari et al, 2022 ; Parmar et al, 2022 ; Sahoo et al, 2022 ; Sharma et al, 2022 ). However, it has been observed in tomatoes that the dominance component was higher than the additive component for shelf life ( Pavan and Gangaprasad, 2022 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%
“…Biofortification can be done by understanding the genes, pathways and regulatory networks responsible for absorbing and transporting nutrients and adopting genetic means that involve using the natural germplasm during conventional breeding, genetic engineering (through genetic engineering or production of transgenics) and other OMICS approaches. The significance of multiomics, nutriomics and foodomics have been explained for development of desirable genotypes with potential microgreen related traits (shelf life and nutrient content) those will be also helpful for improvement of breeding cycles ( Kalia and Singh, 2018 ; Mathiazhagan et al, 2021 ; Reda et al, 2021 ; Valdes et al, 2021 ; AieseCigliano et al, 2022 ; Bansal et al, 2022a ; Chakravorty et al, 2022 ; Dutta et al, 2022 ; Kumari et al, 2022 ; Parmar et al, 2022 ; Sahoo et al, 2022 ; Sharma et al, 2022 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multi-omics investigation of a tomato landrace found that almost half of the deferentially expressed genes were possibly up-regulated and that hundreds of genes were differently expressed at the red ripe stage and throughout postharvest. 36 Table 2 summarizes the application of omic technologies to determine virulence factors during fruit−pathogen interactions.…”
Section: Proteomicsmentioning
confidence: 99%